Emerging, Emergent, Emergence: Boundary Maintenance, Definition Construction, and Legitimation Strategies in the Establishment of a Post‐Evangelical Subculture. Issue 2 (2nd August 2017) - Cooper, Travis Warren
Abstract : Extending social anthropologist Mary Douglas's theory of purity and danger, this article employs a form of textual and discourse analysis and draws on subcultural identity theory. The article argues that one central aspect of social formation occurs through definitional battles or arguments situating theological boundaries and setting the socioreligious parameters of an inchoate group. The Emerging Church Movement (ECM) offers a clear example of discursive scrimmaging. In the late 1990s and 2000s, insiders sought to legitimate the movement through a series of strategies. Published definitions and descriptions worked to establish the normative agenda of the movement and in applying methods of hyper‐specification and internal categorical nuance vied with one another over criteria lists and theological validity. Critical outsiders attempted to discredit the nascent ECM through an inverse set of gate‐keeping strategies. This article underscores the centrality of language, print text, and media in the production of new subcultural identities and suggests that the ECM's effective problematization by gatekeepers has marked the movement as dangerous to evangelicalism's traditional boundaries, thus compelling the emergence, via textual discourse, of a quasi‐ or post‐evangelical identity.